KP-10/Gpr54 attenuates rheumatic arthritis through inactivating NF-κB and MAPK signaling in macrophages. (September 2021) - Wang, Dongsheng; Wu, Zhixiang; Zhao, Chenglong; Yang, Xinghai; Wei, Haifeng; Liu, Mingyao; Zhao, Jian; Qian, Ming; Li, Zhenxi; Xiao, Jianru
Abstract: Rheumatoid arthritis (RA) is an autoimmune disease mainly characterized as chronic inflammation of joint. Both genetic and environmental factors play important roles in RA progression. G protein-coupled receptor 54 (GPR54) and Kisspeptins (KPs), the natural GRP54 ligands encoded by Kiss-1 gene are known to play important roles in immune regulation but the precise role of KP-10/GPR54 in RA remains elusive. Kiss1/Gpr54 expression was determined by immunohistochemistry on protein and real-time PCR on RNA from isolated RA-patient synovial tissue and PBMC. Collagen-induced arthritis (CIA) mouse models were used to investigate the effect of KP-10/Gpr54 on the rheumatic arthritis severity in the mice. The signaling pathway involved in KP-10/GPR54 was assessed by western blot and immunofluorescence.In the present study, we demonstrated that GPR54 upregulation in bone marrow-derived macrophages (BMDM) was associated with the severity of RA. In addition, Gpr54 -/- increased the inflammatory cytokines induced by lipopolysaccharide (LPS) in BMDM and diseased severity of CIA (n = 10), while KP-10 reduced the LPS-induced inflammatory cytokines in vitro and ameliorated the CIA symptoms in vivo. Furthermore, we demonstrated that KP-10/GPR54 binds to PP2A-C to suppressed LPS induced NF-κB and MAPK signaling in BMDM. All these findings suggest that KP-10/GPR54 may be a novel therapeutic target for the diagnosis and treatment of RA. Graphical Abstract: The in vivo data indicated Gpr54 −/− increased the inflammatory cytokines induced by LPS in BMDM, and KP-10/Gpr54 targeted the LPS-induced inflammatory cytokines through NF-κB and MAPK pathway in RAW264.7 cells. The in vivo data indicated Gpr54 −/− increased the diseased severity of CIA, and KP-10 ameliorated the CIA symptoms in DBA/1 J mice. ga1 Highlights: GPR54 is upregulated in RA tissue and positively correlated with the disease severity. Gpr54 −/− increases the number of macrophages in the paws of CIA modeled mice. GPR54 −/− promoted LPS induced inflammation in vitro and CIA induced arthritis symptoms in vivo. KP-10 inhibited LPS induced inflammation in vitro and CIA induced arthritis symptoms in vivo. KP-10 negatively regulates LPS-induced NF-KB and MAPK signaling pathways.